Jhon Fiske Semiotics Analysis In The Theme Of Gender Equality In The Film “Mulan” (Pena Cendekia Insani, 2022)
Film is one of the mass communication media that displays a series of moving images with a storyline played by the actors who are produced to convey a message to the audience. For this reason, the message contained in the film becomes an important point for the community. One of the films that contains many messages in it is the film